El teatro negro contemporáneo como posibilidad de praxis crítica interseccional - de Andrade Silva, Bianca Camila (2023)
Since the Brazilian black theater groups are growing up in cities such as São Paulo and other capitals from Brazil, it becomes necessary to investigate the impact of their productions and organizations in aesthetic, political, and cultural perspectives. In the work of Abdias do Nascimento, black theater used to be proposed as a way to reflect on its identity. This characteristic remains until the present with different demands and prisms. The aim of this paper is to analyze the contemporary play IDA, a work that has the identity as theme for the Brazilian black women, considering identity in its fragmentations and intersections. As a result, it is expected to offer a better understanding of both the political and aesthetic possibilities of contemporary black performing arts, especially in the face of identity disputes as intersectional critical praxis.